Unveiling the Potential of Agricultural Soil Loss Mitigation in Poland: Assessing Conservation Management and Support Practices - Paweł Marcinkowski (Agronomy)
This study aims to evaluate soil erosion mitigation strategies in Poland’s agricultural landscapes by applying the Revised Soil Loss Equation (RUSLE) model to identify high-risk areas where excessive soil loss adversely affects agricultural sustainability and productivity. Scenario assessments were conducted to evaluate the effectiveness of specific conservation practices—contour farming, reduced tillage, and cover crops—by simulating changes in the C-factor (cover-management factor) and P-factor (support practices factor) within the RUSLE framework. The research revealed heightened soil erosion rates during the summer months, particularly in regions with steep slopes and loess formations. Analysis indicated that annual soil loss from arable lands in Poland totals approximately 4.65 Mt yr−1 and that contour farming, reduced tillage, and cover crops could collectively reduce this amount by up to 47%, with the highest reduction observed during the summer period. These findings highlighted the urgent need for stakeholders to adopt sustainable land management strategies. By quantifying the impact of these management practices on soil erosion rates, the study provided insights into the effectiveness of soil conservation measures in reducing erosion risks within Poland’s agricultural landscapes. This study emphasizes the importance of adopting sustainable land management strategies to preserve soil integrity and maintain agricultural productivity in Poland.